Efficacy of Primary Collagen Cross-Linking with Photoactivated Chromophore (PACK-CXL) for the Treatment of Staphylococcus aureus–Induced Corneal Ulcers. Issue 10 (October 2015) - Tal, Kfir; Gal-Or, Orly; Pillar, Shani; Zahavi, Alon; Rock, Oded; Bahar, Irit
Abstract : Purpose: To evaluate the efficacy of corneal collagen cross-linking (CXL) with photoactivated riboflavin (PACK-CXL) as primary therapy for Staphylococcus aureus –induced corneal ulcers in a rabbit model. Methods: The right eye of 40 rabbits was inoculated with S. aureus to induce formation of central corneal ulcers (day 1). The ulcer was examined on day 5, and rabbits were randomly assigned to 4 groups—group A: no treatment (control); group B: topical antibiotic treatment (cefazolin 50 mg/mL, garamycin 14 mg/mL drops, chloramphenicol 5% ointment every 2 hours); group C: PACK-CXL; group D: PACK-CXL + topical antibiotics. Follow-up by biomicroscopy was performed on day 5 and then every week for 1 month. The main outcome measures included infiltrates or the scar diameter, time to healing, time to full epithelialization, and a change in corneal thickness. Results: After 1 month of treatment, group C ulcers had the smallest mean scar diameter (8.8 mm 2 ), followed by groups D (11.2 mm 2 ), B (13.0 mm 2 ), and A (24.5 mm 2 ) ( P = 0.011). Group C had the shortest mean healing time (15.5 days), followed by groups D (17.2 days), B (19.7 days), and A (21.8 days). Analysis of relative reduction in the infiltrate size from day 5 yielded better results for groups C ( P = 0.039) and D ( P = 0.034) than those of group B. Conclusions: We demonstrate a beneficial effect of PACK-CXL as primary treatment, either as stand-alone or as an adjuvant to antimicrobial therapy.